Silver-loaded nanoparticles affect ex-vivo mechanical behavior and mineralization of dentin - Toledano, Manuel (Med Oral Patol Oral Cir Bucal, 2019)
BACKGROUND: The aim was to evaluate the effect of silver loaded nanoparticles (NPs) application on the triboscopic, crystallographic and viscoelastic properties of demineralized dentin. Polymethylmetacrylate-based NPs and Ag loaded NPs were applied on demineralized dentin. MATERIAL AND METHODS: Treated and untreated surfaces were probed by a nanoindenter to test viscoelasticity, and by atomic force microscopy to test nanoroughness and collagen fibril diameter. X-ray diffraction and transmission electron microscopy through selected area diffraction and bright-field imaging were also used. RESULTS: Dentin treated with Ag-NPs attained the lowest complex modulus, and the highest tan delta values after 7 days of storage. Dentin treated with undoped-NPs achieved the lowest nanoroughness and the greatest collagen bandwidths among groups. Crystals were identified as hydroxyapatite with the highest crystallographic maturity and crystallite size in dentin treated with undoped-NPs. Texture increased in all samples from 24 h to 7 d, except in dentin surfaces treated with Ag-NPs at 310 plane. Polyhedral, block-like, hexagonal or plate-like shaped apatite crystals constituted the bulk of minerals in dentin treated with Ag-NPs, after 7 d. Polyhedral or rounded/drop-like, and polymorphic in strata crystal apatite characterized the minerals when undoped-NPs were used, with more crystalline characteristics after 7 d than that found when Ag-NPs were applied. Ag-NPs application did not improve the mechanical performance of dentin and did not produce dentin remineralization. However, energy was dissipated through the dentin without showing stress concentration; contrary was occurring at dentin treated with undoped-NPs, that provoked bridge-like mineral deposits at the dentin surface. CONCLUSIONS: Ag-NPs application did not enhance the mechanical properties of cervical dentin, though the energy dissipation did not damage the dentin structure. Remineralization at dentin was not produced after Ag-NPs application, though improved crystallinity may lead to increase stability of the apatite that was generated at the dentin surface. Key words:Dentin, mechanical, mineralization, roughness, silver, viscoelastic.